COMPARATIVE CHARACTERISTICS THERAPEUTIC EFFECTIVENESS OF THE VITAMIN-MINERAL COMPLEX "BIOFERRON" AND OTHER IRON-CONTAINING PREPARATIONS IN ADOLESCENT GIRLS WITH DIFFERENT DEGREES OF SEVERITY OF IRON DEFICIENCY - Atadjanova , Шаира; Akhmedova, Дилором; Shavazi , Нурали; Rustamov, Мардон (International Journal of Scientific Pediatrics, 2023)
Abstract: The tasks of prevention, diagnosis and treatment of IDA are extremely relevant and priority for health care in many countries of the world, including in Uzbekistan. The purpose of this scientific work was to trace the dynamics of the therapeutic effectiveness of the vitamin-mineral complex “bioferron” and other iron-containing preparations in teenage girls with varying degrees of severity of iron deficiency. Material and methods: The subjects of the study were 177 teenage girls aged 12–14 years, respectively, with LID (45), mild IDA (56) and moderate severity (25) and a control group (51). The source material for determining the number of schoolchildren in the city of Andijan was the list (alphabetical) of students aged 7–14 years (12,000). From this number of students, 1200 children aged 7–14 years (10% sample) were selected using the Bradford table. General clinical, instrumental, biochemical and statistical methods for processing the results were used. Results and discussions: by the end of the saturation period, the Hb level increased statistically significantly in all observation groups (<0.001). There is a pattern that the more severe the severity of ID, the more intense the increase in Hb during the period of saturation of the body with iron. If by the end of the saturation period in girls with LID during treatment with Bioferon, the increase in Hb averaged 7.0 g/l, then this figure for IDA degrees I and II was 27.0 and 33.6 g/l (<0.001), respectively. When prescribing the drug Ferrum-Lek, the increase in Hb in the groups of LAD, IDA of I and II severity was 4.8, 29.1, and 36.5 g/l, respectively, and with the combined use of Bioferron and Ferrum-Lek, respectively 5.9, 27 .7 and 35.4 g/l (p<0.01). Conclusions: The isolated use of the drug "Bioferron" is more effective in correcting relatively mild forms of ID (LID). With I and II degrees of severity of IDA in adolescent girls, the effectiveness of therapy is significantly improved with the combined use of Bioferron and Ferrum-Lek than with both drugs used in isolation.